Peranan Dkwah Pesantren Persatuan Islam 84 dalam Pemahaman Keagamaan Masyarakat Ciganitri Desa Cipagalo Kecamatan Bojong Soang Kabupaten Bandung - M. Fulki Firdaus (Bandung Conference Series: Islamic Broadcast Communication, 2023)
Abstract. The Islamic Unity Islamic Boarding School 84 is located in the Ciganitri area, Cipagalo Village, Bojongsoang District, the community knows it is not only a pesantren, but an icon of Islamic teachings based on the Quran - Sunnah, the existence of a pesantren is certainly expected to have a role for the surrounding community, do people feel the positive impact of its existence? Islamic Unity Islamic Boarding School 84 Ciganitri. Based on this phenomenon, the problems in this research are formulated as follows: (1) How is the Religious Understanding of the Ciganitri Community in Cipagalo Village, Bandung Regency? (2) Da'wah Program What does the Islamic Unity Islamic Boarding School 84 Ciganitri Cipagalo Village Bandung Regency do? (3) What is the Role of Da'wah at the Islamic Unity Islamic Boarding School 84 in Understanding the Religion of the Ciganitri Community in Cipagalo Village, Bandung Regency? This study uses qualitative research through field research with a phenomenological approach to the Ciganitri Community, Cipagalo Village, Bojongsoang District, Bandung Regency. The purpose of the research was to obtain data on how the religious understanding of the Ciganitri Community, Cipagalo Village, Bandung Regency and the Da'wah Program implemented by the Islamic Unity Islamic Boarding School 84 Ciganitri, Cipagalo Village, Bandung Regency and what is the role of preaching at the Islamic Unity Islamic Boarding School 84. The results of this study were to find out the role of da'wah organized by Islamic Unity Islamic Boarding Schools on the religious understanding of the Ciganitri Community, Cipagalo Village, Bojongsoang District, Bandung Regency. Abstrak. Pesantren Persatuan Islam 84 berada di daerah Ciganitri Desa Cipagalo Kecamatan Bojongsoang Kabupaten, masyarakat mengenalnya tidak hanya sebuah pesantren, melainkan sebuah ikon ajaran keislaman yang berbasis Quran – Sunnah, adanya sebuah pesantren tentu diharapkan memiliki peranan bagi masyarakat sekitar, apakah masyarakat merasakan dampak positif dari adanya Pesantren Persis 84 Ciganitri. Berdasarkan fenomena tersebut, maka pemasalahan dalam penelitan ini dirumuskan sebagai berikut: (1) Bagaimana Pemahaman Keagamaan Masyarakat Ciganitri Desa Cipagalo Kabupaten Bandung? (2) Program Dakwah Apa yang dilakukan Pondok Pesantren PERSIS 84 Ciganitri Desa Cipagalo Kabupaten Bandung? (3) Bagaimana Peranan Dakwah Pesantren Persatuan Islam 84 dalam Pemahaman Keagamaan Masyarakat Ciganitri Desa Cipagalo Kabupaten Bandung? Penelitian ini menggunakan penelitian kualitatif melalui penelitian lapangan dengan pendekatan fenomenologi terhadap masyarakat Masyarakat Ciganitri Desa Cipagalo Kecamatan Bojongsoang Kabupaten Bandung. .Adapun tujuan penelitian, adalah untuk memperoleh data Bagaimana Pemahaman Keagamaan Masyarakat Ciganitri Desa Cipagalo Kabupaten Bandung. dan Program Dakwah yang dilaksanakan Pesantren Persatuan Islam 84 Ciganitri Desa Cipagalo Kabupaten Bandung serta Bagaimana Peranan dakwah Pondok Pesantren PERSIS 84 dalam Pemahaman Keagamaan Masyarakat Ciganitri Desa Cipagalo Kabupaten Bandung. Hasil penelitian ini adalah untuk mengtetahui bagaimana peranan dakwah yang diselenggarakan oleh Pesantren Persatuan Islam terhadap pemahaman keagamaan Masyarakat Ciganitri Desa Cipagalo Kecamatan Bojongsoang Kabupaten Bandung.